Lithium-boron alloy negative electrode, preparation method thereof and lithium metal battery

By preparation of lithium boron alloy negative electrodes of lithium boron alloy of lithium boron alloy, lithium metal negative electrodes of lithium branches and volume expansion are solved, which significantly improves the cycle life and safety of the battery.

CN119361614AInactive Publication Date: 2025-01-24HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411263361.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium metal negative electrodes are prone to form lithium dendrites and volume expansion in liquid batteries, resulting in reduced efficiency of circulation, shortened life, and safety hazards.

Method used

The lithium boron alloy anode is prepared by sealing the tube at high temperature and melting it. The lithium metal and boron powder are sealed in a metal tube filled with inert gas, and then vacuum calcined at high temperature to mix and melt to form a lithium boron alloy anode.

Benefits of technology

It effectively suppresses the generation and volume expansion of lithium dendrites, improves the cycle life and safety of the battery, and achieves stable cycling for more than 1500 hours under the conditions of 1mA/cm2 and 5mAh/cm2, with a polarization voltage of only about 7mV.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361614A_ABST
    Figure CN119361614A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium metal batteries, in particular to a lithium-boron alloy negative electrode, a preparation method thereof and a lithium metal battery. The preparation method of the lithium-boron alloy negative electrode comprises the following steps: sealing lithium metal and boron powder in a metal tube filled with inert gas, packaging the metal tube in a quartz tube in vacuum, and carrying out high-temperature calcination on the quartz tube, so that the lithium metal and the boron powder in the metal tube are mixed and molten to obtain the lithium-boron alloy negative electrode. According to the preparation method, a tube sealing high-temperature melting method is adopted, so that the reaction atmosphere and high-temperature melting conditions in the preparation process of the lithium-boron alloy negative electrode are ensured, and the high-purity and stable lithium-boron alloy negative electrode is simply and efficiently prepared. The surface of the prepared lithium-boron alloy negative electrode has a unique nanofiber structure, generation of lithium dendrites can be effectively inhibited, volume expansion can be inhibited, rapid and uniform deposition of lithium ions in the cycle process of a battery can be adjusted, and the cycle life of the battery is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium metal batteries, and in particular to a lithium-boron alloy negative electrode and a preparation method thereof, and a lithium metal battery. Background Art

[0002] Although lithium batteries have profoundly changed our daily lives, after nearly 30 years of development, lithium batteries still face major challenges: (1) The actual energy density is close to the theoretical limit, and lithium-ion batteries are far from meeting major development needs, which limits multi-scenario applications; (2) Safety issues; (3) Insufficient adaptability to extreme environments, especially in extreme environments such as underwater deep-sea exploration and space exploration, which require better adaptability. As for the negative electrode of lithium batteries, metallic lithium has an extremely high specific capacity of 3860mAh / g, while the theoretical specific capacity of traditional negative electrode materials (graphite) is only 372mAh / g. Therefore, the use of lithium metal negative electrodes can greatly improve the energy density of lithium batteries, significantly increase the battery capacity, and improve the battery life. Lithium metal also has the lowest reduction potential (-3.040V compared to the standard hydrogen electrode), which can provide a higher operating voltage for the battery as a whole under the condition of a certain redox potential of the positive electrode material, thereby improving the battery's energy density. Therefore, lithium metal negative electrodes have become the research focus of the next generation of battery development. However, existing research results show that in liquid batteries, on the one hand, the metallic lithium negative electrode will inevitably form lithium dendrites and expand in volume, which will reduce the battery's cycle coulomb efficiency and shorten the battery life. It will also pierce the diaphragm and cause a short circuit, leading to the risk of thermal runaway and explosion. On the other hand, it will also consume a large amount of electrolyte, accelerate battery failure, and reduce cycle life. In solid-state batteries, although the lithium dendrite problem has been significantly suppressed, the interface contact problem between the lithium metal negative electrode and the solid electrolyte seriously affects its practical application.

[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a lithium-boron alloy negative electrode and a preparation method thereof and a lithium metal battery, aiming to solve the problem that the existing lithium metal negative electrode is prone to form lithium dendrites and volume expansion in liquid batteries.

[0005] The technical solution of the present invention is as follows:

[0006] A first aspect of the present invention provides a method for preparing a lithium-boron alloy negative electrode, comprising the steps of:

[0007] The lithium metal and boron powder are sealed in a metal tube filled with an inert gas, the metal tube is vacuum-sealed in a quartz tube, and the quartz tube is calcined at a high temperature so that the lithium metal and boron powder in the metal tube are mixed and melted to obtain the lithium-boron alloy negative electrode.

[0008] Optionally, the mass ratio of the lithium metal to the boron powder is 85-95:5-15.

[0009] Optionally, the high-temperature calcination temperature is 600° C. to 800° C., and the insulation time is 6 h to 8 h.

[0010] Optionally, the metal tube is a niobium tube or a tantalum tube.

[0011] Optionally, the inert gas is argon, and the pressure of the inert gas in the metal tube is 3×10 4 Pa~5×10 4 Pa.

[0012] Optionally, the vacuum degree in the quartz tube is less than or equal to 1×10 5 Pa.

[0013] Optionally, the step of calcining the quartz tube at a high temperature so that the lithium metal and the boron powder in the metal tube are mixed and melted to obtain the lithium-boron alloy negative electrode specifically includes:

[0014] The quartz tube is calcined at 600° C. to 800° C. for 6 h to 8 h, so that the lithium metal and boron powder in the metal tube are mixed and melted to obtain a lithium-boron alloy block, and then the lithium-boron alloy block is repeatedly rolled to obtain a lithium-boron alloy negative electrode.

[0015] The second aspect of the present invention provides a lithium-boron alloy negative electrode, which is prepared by the preparation method of the present invention.

[0016] Optionally, the mass fraction of boron in the total mass of the lithium-boron alloy negative electrode is 5% to 20%.

[0017] Optionally, the surface of the lithium-boron alloy negative electrode has a nanofiber structure, and the fiber diameter of the nanofiber structure is 20nm to 100nm.

[0018] A third aspect of the present invention provides a lithium metal battery, comprising the lithium-boron alloy negative electrode described in the present invention.

[0019] Beneficial effect: The present invention adopts the method of sealing tube high temperature melting to ensure the reaction atmosphere and high temperature melting conditions in the preparation process of lithium-boron alloy negative electrode, and simply and efficiently prepares a high-purity and stable lithium-boron alloy negative electrode. The surface of the prepared lithium-boron alloy negative electrode has a unique nanofiber structure, which can effectively inhibit the formation of lithium dendrites and inhibit volume expansion, and can regulate the rapid and uniform deposition of lithium ions during the battery cycle, greatly improving the cycle life of the battery, and finally achieving a battery capacity of 1mA / cm 2 , 5mAh / cm 2 Under the same conditions, it can cycle stably for more than 1500 hours, and the polarization voltage is only about 7mV. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention provides a process flow chart of a method for preparing a lithium-boron alloy negative electrode.

[0021] Figure 2 This is the XRD spectrum of the lithium-boron alloy negative electrode prepared in Example 1-3.

[0022] Figure 3 The SEM images of the lithium-boron alloy negative electrode with a boron mass fraction of 5% in Example 1 are shown at different magnifications.

[0023] Figure 4 The SEM images of the lithium-boron alloy negative electrode with a boron mass fraction of 10% in Example 2 are shown at different magnifications.

[0024] Figure 5 The SEM images of the lithium-boron alloy negative electrode with a boron mass fraction of 15% in Example 3 are shown at different magnifications.

[0025] Figure 6 a in the figure is the deposition overpotential curve of the lithium-boron alloy negative electrode prepared in Examples 1-3 and the pure lithium metal negative electrode prepared in Comparative Example 1, Figure 6 b is a histogram of the deposition overpotential of the lithium-boron alloy negative electrode prepared in Examples 1-3 and the pure lithium metal negative electrode prepared in Comparative Example 1.

[0026] Figure 7 a in the equation is 1 mA / cm 2 , 1mAh / cm 2 Long cycle performance diagram of four symmetrical batteries under conditions, Figure 7 b in the equation is 1 mA / cm 2 , 3mAh / cm 2 Long cycle performance diagram of four symmetrical batteries under different conditions.

[0027] Figure 8 a in the equation is 1 mA / cm 2 , 5mAh / cm 2 Long cycle performance diagram of LiB 10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions, Figure 8 b in the equation is 5 mA / cm 2 , 5mAh / cm 2 Long cycle performance diagram of LiB 10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions.

[0028] Fig. 9 a in the equation is 5 mA / cm 2 , 10mAh / cm2 Long cycle performance diagram of LiB 10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions, Fig. 9 b in the equation is 10 mA / cm 2 , 10mAh / cm 2 Long cycle performance diagram of LiB 10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions, Fig. 9 c is at 10mA / cm 2 , 15mAh / cm 2 Long cycle performance diagram of LiB10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under different conditions.

[0029] Fig.10 a and b are Li / / Li symmetric cells at 1 mA / cm 2 , 3mAh / cm 2 SEM image of the negative electrode surface after 50 cycles under the same conditions. Fig.10 c and d in the figure are LiB 10% / / LiB 10% symmetric cell at 1 mA / cm 2 , 3mAh / cm 2 SEM image of the negative electrode surface after 50 cycles under the same conditions.

[0030] Fig.11 a in the figure is an in-situ optical microscope image of Li deposited on a pure lithium metal anode at different times. Fig.11 Figure b is an in-situ optical microscope image of Li deposited on the lithium-boron alloy negative electrode at different times.

[0031] Fig.12 a is the rate performance and coulombic efficiency data of LiB 10% LFP full battery and Li LFP full battery, Fig.12 Figure b is the discharge capacity data of LiB 10% LFP full battery and Li LFP full battery under different rate conditions.

[0032] Fig.13 a is the schematic diagram of LiB / / LFP soft pack battery and the long cycle performance diagram, Fig.13 b in the figure is the schematic diagram of Li / / LFP soft-pack battery and the long cycle performance diagram. DETAILED DESCRIPTION

[0033] The present invention provides a lithium-boron alloy negative electrode and a preparation method thereof and a lithium metal battery. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0034] Lithium alloys used as negative electrodes in lithium metal batteries are expected to increase the capacity and service life of the batteries. However, due to the high reactivity of lithium metal, it is easy to react with air to produce products such as Li2O, Li2CO3 and LiOH and lose its activity. Therefore, the preparation process of lithium alloys has high requirements for the reaction atmosphere. In order to ensure the atmosphere for alloy smelting, it is usually chosen to be smelted in a glove box, but the temperature of the heating table in the glove box is limited and high-temperature smelting cannot be performed. In addition, the large space of the glove box will result in a certain amount of water and oxygen, and high-purity lithium alloys cannot be obtained. In addition, boron is quite abundant in nature, and lithium-boron alloys have great application prospects in lithium metal batteries. Based on this, an embodiment of the present invention provides a method for preparing a lithium-boron alloy negative electrode, which includes the steps of:

[0035] The lithium metal and boron powder are sealed in a metal tube filled with an inert gas, the metal tube is vacuum-sealed in a quartz tube, and the quartz tube is calcined at a high temperature so that the lithium metal and boron powder in the metal tube are mixed and melted to obtain the lithium-boron alloy negative electrode.

[0036] The embodiment of the present invention uses lithium metal and boron powder as raw materials, and adopts the method of sealing tube high temperature melting to prepare the lithium boron alloy negative electrode. First, the lithium metal and the boron powder are sealed in a metal tube filled with inert gas. The inert gas in the metal tube ensures the high temperature smelting reaction atmosphere of the lithium metal and the boron powder, and is isolated from the external air. Then the metal tube is sealed in a vacuum quartz tube, which further ensures the reaction atmosphere of the high temperature smelting of the lithium boron alloy negative electrode. Finally, the sealed quartz tube is calcined at high temperature, so that the lithium metal and the boron powder in the metal tube are mixed and melted, and the lithium boron alloy negative electrode is obtained. The method of the embodiment of the present invention is simple and efficient, which ensures the reaction atmosphere and high temperature smelting conditions of the lithium boron alloy negative electrode preparation process, and prepares a high-purity and stable lithium boron alloy negative electrode.

[0037] In one embodiment, the mass ratio of the lithium metal and the boron powder is 85-95:5-15. The embodiment of the present invention utilizes boron doping to alloy the lithium metal negative electrode, so the amount of boron powder used is relatively small. Within this mass ratio range, a nanofiber structure with a stable morphology is formed on the surface of the prepared lithium-boron alloy. The optimal ratio of lithium-boron alloy and lithium metal can effectively induce uniform deposition of lithium ions and ensure the stable morphology of the lithium-boron alloy fiber structure during the cycle. Too much lithium-boron alloy skeleton will collapse during the cycle, causing battery failure, and will also reduce the theoretical capacity of the negative electrode. Too little lithium-boron alloy cannot adjust the uniform deposition of lithium ions, and the effect of improving dendrites is not obvious.

[0038] In one embodiment, the high temperature calcination temperature is 600°C to 800°C, the holding time is 6h to 8h, and the heating rate is 5°C / min. Within this temperature and holding time range, the lithium metal is melted and uniformly mixed with the boron powder to ensure the successful synthesis and uniform distribution of Li5B4.

[0039] In one embodiment, the metal tube is a niobium tube or a tantalum tube. The niobium tube or the tantalum tube will not react with lithium metal or boron powder, has a high melting point, and has good sealing performance. The inert gas filled therein ensures a high-temperature smelting reaction atmosphere for lithium metal and boron powder.

[0040] In one embodiment, the inert gas is argon, and the pressure of the inert gas in the metal tube is 3×10 4 Pa~5×10 4 Pa. Within the pressure range, it is possible to ensure that lithium metal is not oxidized by air, avoid the introduction of impurities during the melting process, and ensure the purity of the lithium-boron alloy negative electrode.

[0041] In one embodiment, the vacuum degree in the quartz tube is less than or equal to 1×10 5 Pa. Within the vacuum range, the stability of the metal tube is ensured at high temperature, and it will not react with oxygen to destroy the airtightness of the metal tube, and will not introduce impurities into the lithium-boron alloy negative electrode, thereby ensuring the purity of the lithium-boron alloy negative electrode.

[0042] In one embodiment, lithium metal and boron powder are sealed in a metal tube filled with an inert gas by electric arc packaging, wherein the electric arc generates high temperature to melt the metal tube and achieve packaging.

[0043] In one embodiment, the quartz tube is calcined at a high temperature so that the lithium metal and the boron powder in the metal tube are mixed and melted to obtain the lithium-boron alloy negative electrode, and the steps specifically include:

[0044] The quartz tube is calcined at 600° C. to 800° C. for 6 h to 8 h, so that the lithium metal and boron powder in the metal tube are mixed and melted to obtain a lithium-boron alloy block, and then the lithium-boron alloy block is repeatedly rolled to obtain a lithium-boron alloy negative electrode.

[0045] In this embodiment, the lithium-boron alloy block can be repeatedly rolled using a roller press, so that a uniform lithium-boron alloy negative electrode can be prepared, and the lithium-boron alloy block can be rolled into a desired negative electrode shape as needed, for example, the lithium-boron alloy block can be rolled into a disc shape, etc.

[0046] In one embodiment, the quartz tube is calcined at high temperature using a high temperature melting device, so that the lithium metal and boron powder in the metal tube are mixed and melted to obtain the lithium-boron alloy negative electrode, wherein the high temperature melting device is capable of calcining the material at high temperature, for example, it can be a muffle furnace.

[0047] An embodiment of the present invention further provides a lithium-boron alloy negative electrode, which is prepared using the preparation method described in the present invention.

[0048] In one embodiment, the lithium-boron alloy negative electrode comprises metallic lithium and boron, and the lithium-boron alloy negative electrode is prepared by the preparation method of the present invention.

[0049] In one embodiment, the mass fraction of boron in the total mass of the lithium-boron alloy negative electrode is 5% to 20%.

[0050] In a preferred embodiment, the mass fraction of boron in the total mass of the lithium-boron alloy negative electrode is 5% to 15%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.

[0051] In a more preferred embodiment, the mass fraction of boron in the total mass of the lithium-boron alloy negative electrode is 10%. The lithium-boron alloy negative electrode at this mass fraction has the best electrochemical lithium deposition / stripping stability, and the prepared battery has the advantages of long cycle life, high capacity retention rate, good rate performance, etc., at 1 mA / cm 2 , 5mAh / cm 2 Under the same conditions, it can cycle stably for more than 1500 hours, and the polarization voltage is only about 7mV.

[0052] In one embodiment, the surface of the lithium-boron alloy negative electrode has a nanofiber structure, and the fiber diameter of the nanofiber structure is 20nm to 100nm, for example, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm. The surface of the lithium-boron alloy negative electrode has this unique nanofiber structure, which can provide a certain space and support strength for the deposition of lithium, induce the uniform deposition of lithium and inhibit volume expansion. Therefore, during the battery cycle, the rapid and uniform deposition of lithium ions can be adjusted, thereby effectively inhibiting the generation of lithium dendrites and inhibiting volume expansion, and improving the cycle life of the battery.

[0053] In one embodiment, the lithium-boron alloy negative electrode is in the shape of a disc, the thickness of the disc is 150 to 250 μm, and the diameter of the disc is 8 to 12 mm.

[0054] The present invention also provides a lithium metal battery, which includes the lithium-boron alloy negative electrode of the present invention. The battery can effectively improve the phenomenon of lithium dendrites and volume expansion of the lithium metal negative electrode during the cycle process, and has the advantages of long cycle life, high capacity retention rate, good rate performance, etc.

[0055] The present invention will be further described below by means of specific examples.

[0056] Example 1

[0057] This embodiment provides a lithium-boron alloy negative electrode and a preparation method thereof, which are specifically as follows:

[0058] like Figure 1 As shown in the figure, 471.8 mg of lithium metal (lithium sheet) and 24.8 mg of boron powder are placed in a metal tube (niobium tube). The lithium metal and boron powder are sealed in the metal tube filled with argon gas by arc encapsulation. The pressure is 4×10 4 Pa, the metal tube is placed in a quartz tube for vacuum sealing, and the vacuum degree is less than 1×10 5 Pa, and then the packaged quartz tube is placed in a muffle furnace for high-temperature calcination, wherein the temperature is 700°C, the heating rate is 5°C / min, and the holding time is 6 hours, and the lithium metal and boron powder in the metal tube are mixed and melted. After the completion, the metal tube is disassembled to obtain a lithium-boron alloy block, and then the lithium-boron alloy block is rolled into a sheet with a thickness of 200μm by a roller press, and it is cut into a disc with a diameter of 8-12mm, that is, a lithium-boron alloy negative electrode is prepared, wherein the mass fraction of boron in the lithium-boron alloy negative electrode is 5%.

[0059] Example 2

[0060] The preparation method of Example 2 is the same as that of Example 1, except that the amount of boron powder is adjusted to 52.4 mg, thereby preparing a lithium-boron alloy negative electrode, wherein the mass fraction of boron in the lithium-boron alloy negative electrode is 10%.

[0061] Example 3

[0062] The preparation method of Example 3 is the same as that of Example 1, except that the amount of boron powder is adjusted to 83.3 mg, thereby preparing a lithium-boron alloy negative electrode, wherein the mass fraction of boron in the lithium-boron alloy negative electrode is 15%.

[0063] Figure 2It is the XRD spectrum of the lithium-boron alloy negative electrode prepared in Examples 1-3, wherein LiB 5% represents the lithium-boron alloy negative electrode with a boron mass fraction of 5% prepared in Example 1, LiB 10% represents the lithium-boron alloy negative electrode with a boron mass fraction of 10% prepared in Example 2, and LiB 15% represents the lithium-boron alloy negative electrode with a boron mass fraction of 15% prepared in Example 3. According to the figure, the diffraction peaks of the intermetallic compound Li5B4 and metallic lithium are detected in Examples 1-3, and with the increase of the boron content, the intensity of the diffraction peak of the intermetallic compound Li5B4 gradually increases while the intensity of the diffraction peak of the lithium metal gradually decreases, and the diffraction peak of the boron element is not detected in the XRD graph, which indicates that the high-temperature sealed tube melting preparation method of the present invention can achieve a sufficient alloying reaction between lithium and boron. In addition, an amorphous broad peak is formed at 10°-30° in the XRD spectrum, which is the characteristic peak of the polyimide sealing tape used in the sample preparation test process. The sealing tape can protect the lithium-boron alloy negative electrode from air oxidation to a certain extent, avoiding affecting the test results. Finally, although the sample was protected during the sample preparation test, the LiB 15% sample still showed a weak Li2O diffraction peak. This is because the sample was exposed to air oxidation during the test process, but the Li2O diffraction peak position did not overlap with the peak position of the target substance, and did not affect the test results.

[0064] Figure 3 The SEM images of the lithium-boron alloy negative electrode with a boron mass fraction of 5% in Example 1 are shown at different magnifications. Figure 4 The SEM images of the lithium-boron alloy negative electrode with a boron mass fraction of 10% in Example 2 are shown at different magnifications. Figure 5 The SEM images of the lithium-boron alloy negative electrode with a boron mass fraction of 15% in Example 3 are shown at different magnifications. Figure 3-Figure 5 The nanofiber structure on the surface of the lithium-boron alloy negative electrode can be observed, wherein the fiber diameter on the surface of the lithium-boron alloy negative electrode of Example 1 is about 87nm, the fiber diameter on the surface of the lithium-boron alloy negative electrode of Example 2 is about 38nm, and the fiber diameter on the surface of the lithium-boron alloy negative electrode of Example 3 is about 35nm. The above results show that with the increase of the boron content, the fiber diameter of the nanofiber structure on the surface of the lithium-boron alloy negative electrode continues to decrease and the gap between the fibers increases slightly. This in-situ formed nanofiber structure can provide a certain space and support strength for the deposition of lithium, can induce uniform deposition of lithium and inhibit volume expansion.

[0065] Comparative Example 1

[0066] The preparation method of Comparative Example 1 is the same as that of Example 1, except that no boron powder is used, thereby preparing a pure lithium metal negative electrode.

[0067] Example 4

[0068] This example explores the lithium deposition nucleation overpotential of the lithium boron alloy negative electrode prepared in the above examples 1-3 and the pure lithium metal negative electrode prepared in comparative example 1. The specific method is to assemble the battery in the following order in a glove box filled with argon gas and with O2 <0.1ppm, H2O <0.1ppm: positive electrode shell-spring sheet-gasket-positive electrode-diaphragm-electrolyte-negative electrode-gasket-negative electrode shell, wherein the positive electrode shell adopts 2032 type, the negative electrode shell adopts 2032 type, the spring sheet adopts a stainless steel spring sheet with a diameter of 15.8mm, the gasket adopts a stainless steel gasket with a diameter of 15.8mm, the positive electrode adopts a lithium metal sheet with a diameter of 10mm, the diaphragm adopts a 16mm microporous PP film (Celgard 2400), the electrolyte adopts Duoduo Chemical Reagent LS-009 type electrolyte, and the negative electrode adopts a lithium boron alloy negative electrode disc with a diameter of 10mm prepared in examples 1-3 or a pure lithium metal negative electrode disc with a diameter of 10mm prepared in comparative example 1. After the four batteries were left to stand for 6 hours, they were charged at 1 mA / cm 2 Constant current charging is performed under the conditions of

[0069] Figure 6 a in the figure is the deposition overpotential curve of the lithium-boron alloy negative electrode prepared in Examples 1-3 and the pure lithium metal negative electrode prepared in Comparative Example 1, Figure 6 b is the deposition overpotential bar graph of the lithium-boron alloy negative electrode prepared in Examples 1-3 and the pure lithium metal negative electrode prepared in Comparative Example 1. It can be seen from the figure that the pure lithium metal negative electrode in Comparative Example 1 has a deposition overpotential of 1 mA / cm 2 The deposition overpotential under the above conditions is 71.6 mV, while the deposition overpotential of the lithium-boron alloy negative electrode shows a significantly decreasing trend, among which the LiB 10% alloy negative electrode in Example 2 has the lowest deposition overpotential of only 26.7 mV. The above results show that the lithium-boron alloy negative electrode prepared by the present invention can achieve lithium ion (Li + ) is deposited quickly and evenly on the surface, thus effectively inhibiting the formation of lithium dendrites.

[0070] Example 5

[0071] This example explores the electrochemical properties of the lithium-boron alloy negative electrode prepared in the above examples 1-3 and the pure lithium metal negative electrode prepared in comparative example 1.

[0072] The lithium-boron alloy negative electrode prepared in Examples 1-3 and the pure lithium metal negative electrode prepared in Comparative Example 1 are respectively assembled into symmetrical batteries. The assembly method of the symmetrical battery is to assemble the symmetrical battery in a glove box filled with argon gas with O2<0.1ppm, H2O<0.1ppm in the following order: positive electrode shell-spring sheet-gasket-positive electrode-diaphragm-electrolyte-negative electrode-gasket-negative electrode shell, the positive electrode shell adopts 2032 type, the negative electrode shell adopts 2032 type, the spring sheet adopts a stainless steel spring sheet with a diameter of 15.8mm, the gasket adopts a stainless steel gasket with a diameter of 15.8mm, the diaphragm adopts a 16mm microporous PP film (Celgard 2400), the electrolyte adopts Duoduo Chemical Reagent LS-009 type electrolyte, the positive electrode and the negative electrode use the same materials, and the lithium-boron alloy negative electrode disc with a diameter of 10mm prepared in Examples 1-3 or the pure lithium metal negative electrode disc with a diameter of 10mm prepared in Comparative Example 1 is respectively used.

[0073] Four symmetrical batteries were prepared according to the above method, wherein the lithium-boron alloy negative electrode in Example 1 was assembled into a LiB5% / / LiB 5% symmetrical battery, the lithium-boron alloy negative electrode in Example 2 was assembled into a LiB10% / / LiB 10% symmetrical battery, the lithium-boron alloy negative electrode in Example 3 was assembled into a LiB 15% / / LiB15% symmetrical battery, and the pure lithium metal negative electrode in Comparative Example 1 was assembled into a Li / / Li symmetrical battery. Constant current charge and discharge tests were performed on the four prepared symmetrical batteries, and the constant current charge and discharge test method was: after the battery was left to stand for 6 hours, charging and discharging tests were performed at different current densities.

[0074] Figure 7 a in the equation is 1mA / cm 2 , 1mAh / cm 2 Long cycle performance diagram of four symmetrical batteries under conditions, Figure 7 b in the figure is 1 mA / cm 2 , 3mAh / cm 2 The long cycle performance diagram of four symmetrical batteries under the same conditions. The marked Li in the figure represents Li / / Li symmetrical battery, LiB 5% represents LiB 5% / / LiB 5% symmetrical battery, LiB 10% represents LiB 10% / / LiB 10% symmetrical battery, and LiB 15% represents LiB15% / / LiB 15% symmetrical battery. According to the figure, at 1mA / cm 2 , 1mAh / cm 2Under the same conditions, the Li / / Li symmetrical battery showed a voltage drop after 250 hours of cycling, that is, a short circuit occurred. The LiB 5% / / LiB5% symmetrical battery can be stably cycled for 500 hours with an overpotential of only 17mV, and then the polarization voltage increased slightly. The LiB 15% / / LiB15% symmetrical battery can be stably cycled for 400 hours with an overpotential of 23mV, and then the polarization voltage also increased, while the LiB10% / / LiB 10% symmetrical battery can be stably cycled for 750 hours with an overpotential of only 15mV. The above results show that the LiB 10% / / LiB 10% symmetrical battery assembled with the lithium-boron alloy negative electrode prepared in Example 2 has the best electrochemical lithium deposition / stripping stability. On this basis, the surface capacity is increased to 3mAh / cm 2 After that, the Li / / Li symmetric battery can stably cycle for 650h with an overpotential of 19mV, and then the voltage drops sharply at 900h, that is, a short circuit occurs. The LiB 5% / / LiB 5% symmetric battery can stably cycle for 800h with an overpotential of 15mV, and then the polarization voltage increases, and a short circuit occurs when the cycle reaches 1440h. The LiB 15% / / LiB15% symmetric battery can stably cycle for 600h, and then the polarization voltage gradually increases, which indicates that the excess LiB skeleton does not have a positive effect on the stable deposition / stripping of lithium. The LiB 10% / / LiB 10% symmetric battery can stably cycle for 900h with an overpotential of 13mV, and the voltage decreases slightly at 1600h, which may be caused by a micro-short circuit inside the battery.

[0075] In order to explore whether the unique nanofibrous structure on the surface of lithium-boron alloy negative electrode is conducive to the rapid deposition and stripping behavior of large amounts of lithium, constant current charge and discharge tests were carried out on LiB10% / / LiB 10% symmetric cells and Li / / Li symmetric cells at higher areal capacity and larger current density.

[0076] Figure 8 a in the equation is 1mA / cm 2 , 5mAh / cm 2 Long cycle performance diagram of LiB 10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions, Figure 8 b in the figure is 5 mA / cm 2 , 5mAh / cm 2 The long cycle performance diagram of LiB 10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions. According to the figure, at 1mA / cm 2 , 5mAh / cm 2Under the same conditions, the overpotential of the first cycle of the LiB10% / / LiB 10% symmetric battery is 16.7mV, and the overpotential of the first cycle of the Li / / Li symmetric battery is 22.6mV. With the increase in the number of cycles, the overpotential of the LiB 10% / / LiB 10% symmetric battery stabilizes at 7.4mV, and the overpotential of the Li / / Li symmetric battery stabilizes at 12.1mV. The Li / / Li symmetric battery experienced a voltage drop and short circuit at the 70th hour of the cycle, while the LiB 10% / / LiB 10% symmetric battery can stably cycle for 1580h with an overpotential of only 9.6mV, without short circuit, and the cycle life is increased by 21 times. On this basis, the current density is increased to 5mA / cm 2 After that, the deposition overpotential of the Li / / Li symmetric cell was 33.8mV, and the deposition overpotential of the LiB 10% / / LiB 10% symmetric cell was 27.3mV. When the cycle reached 60h, the Li / / Li symmetric cell had a short circuit, while the LiB 10% / / LiB10% symmetric cell could still cycle stably, and only a slight voltage fluctuation occurred at 170h, which may be due to a micro-short circuit but did not cause battery failure. These results show that the lithium-boron alloy negative electrode prepared by the present invention can still maintain rapid deposition and uniform distribution of lithium ions at high current density.

[0077] Fig. 9 a in the equation is 5 mA / cm 2 , 10mAh / cm 2 Long cycle performance diagram of LiB 10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions, Fig. 9 b in the figure is 10 mA / cm 2 , 10mAh / cm 2 Long cycle performance diagram of LiB 10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions, Fig. 9 The c in the figure is 10 mA / cm 2 , 15mAh / cm 2 The long cycle performance diagram of LiB10% / / LiB 10% symmetric battery and Li / / Li symmetric battery under the same conditions. According to the figure, at 5mA / cm 2 , 10mAh / cm 2 Under the same conditions, the Li / / Li symmetrical battery short-circuited after 44 hours of cycling, while the LiB10% / / LiB 10% symmetrical battery could stably cycle for 105 hours, and the cycle life was increased by 2 times. 2 , 10mAh / cm 2Under the conditions, the lithium deposition overpotential of the first cycle of the Li / / Li symmetric battery is 252.7mV, and an obvious short circuit occurs after 20h of cycling, while the first cycle deposition overpotential of the LiB 10% / / LiB 10% symmetric battery is 124.9mV, and it can be stably cycled for 78h at a lower overpotential, and the cycle life is increased by three times. It can be seen that the lithium-boron alloy negative electrode prepared by the present invention can still induce rapid deposition and uniform distribution of lithium ions at high current density. On this basis, the surface capacity is further increased to 15mAh / cm -2 In constant current charge and discharge tests, the Li / / Li symmetrical battery had a short circuit phenomenon after 24 hours of cycling and the voltage polarization was large during the cycling process, while the LiB 10% / / LiB 10% symmetrical battery could stably cycle for 81 hours at an overpotential of 66.0mV, and the cycle life was increased by 2 times. The above results show that the lithium-boron alloy negative electrode prepared by the present invention can still ensure long-term uniform deposition and stable stripping of lithium at high current density, and the unique nanofiber structure ensures the stability of the negative electrode structure and improves the cycle life of the battery.

[0078] Example 6

[0079] This example investigates the electrochemical behavior of the lithium-boron alloy negative electrode with a boron mass fraction of 10% prepared in Example 2 and the pure lithium metal negative electrode prepared in Comparative Example 1.

[0080] The LiB 10% / / LiB 10% symmetric cell and the Li / / Li symmetric cell prepared in Example 5 were subjected to a 1 mA / cm 2 , 3mAh / cm 2 The morphology of the negative electrode was characterized after 50 cycles under the same conditions. Fig.10 a and b are Li / / Li symmetric cells at 1 mA / cm 2 , 3mAh / cm 2 SEM image of the negative electrode surface after 50 cycles under the same conditions. Fig.10 c and d are LiB 10% / / LiB 10% symmetrical battery at 1mA / cm 2 , 3mAh / cm 2 SEM image of the negative electrode surface after 50 cycles under the same conditions. It can be seen from the figure that after 50 cycles of the Li / / Li symmetric battery, the negative electrode surface is rough and more significant lithium dendrites can be observed, while after 50 cycles of the LiB10% / / LiB 10% symmetric battery, the negative electrode surface is flat and smooth, without lithium dendrites, and can maintain a good nanofiber structure, which further verifies that the lithium-boron alloy negative electrode prepared by the present invention can effectively inhibit the formation of lithium dendrites and can regulate the uniform deposition of lithium ions.

[0081] In order to observe the formation process of lithium dendrites more intuitively, the lithium-boron alloy negative electrode with a boron mass fraction of 10% prepared in Example 2 and the pure lithium metal negative electrode prepared in Comparative Example 1 were tested at 2 mA / cm 2 Li was deposited for 60 min under the conditions of , in which in situ microscopic observation technology was introduced. Fig.11 a is an in-situ optical microscope image of Li deposited on a pure lithium metal anode at different times. Fig.11 b in the figure is an in-situ microscope optical image of Li deposited on the lithium-boron alloy negative electrode at different times. According to the figure, when lithium is deposited for 20 minutes, obvious lithium dendrites and uneven lithium deposition appear on the surface of the pure lithium metal negative electrode. When lithium is deposited for 60 minutes, the lithium dendrites on the surface of the pure lithium metal negative electrode are dendritic, which can easily pierce the diaphragm to connect the positive and negative electrodes to form a short circuit, which has certain safety hazards, and the dendritic lithium dendrites can easily break to form "dead lithium", causing irreversible loss of lithium. However, the lithium on the surface of the lithium-boron alloy negative electrode has been uniformly deposited without obvious lithium dendrites. This shows that the lithium-boron alloy negative electrode of the present invention has a good ability to regulate the uniform deposition of lithium ions, and the uniform lithium deposition process inhibits the generation of lithium dendrites, which can solve the safety problems in the practical application of lithium metal negative electrodes and improve battery life to a certain extent.

[0082] Example 7

[0083] This example further explores the practical application capabilities of the lithium-boron alloy negative electrode with a boron mass fraction of 10% prepared in the above Example 2 and the pure lithium metal negative electrode prepared in Comparative Example 1 in a full battery.

[0084] The lithium-boron alloy negative electrode with a boron mass fraction of 10% prepared in Example 2 and the pure lithium metal negative electrode prepared in Comparative Example 1 were assembled into full batteries. The assembly method of the full battery was to assemble the battery in the following order in a glove box filled with argon gas and with O2 < 0.1ppm, H2O < 0.1ppm: positive electrode shell-spring-gasket-positive electrode-diaphragm-electrolyte-negative electrode-gasket-negative electrode shell. The positive electrode shell was 2032 type, the negative electrode shell was 2032 type, the spring was a stainless steel spring with a diameter of 15.8mm, the gasket was a stainless steel gasket with a diameter of 15.8mm, the diaphragm was a 16mm microporous PP film (Celgard 2400), the positive electrode was lithium iron phosphate (LFP), and the surface loading of lithium iron phosphate was controlled at 4mg / cm 2 The electrolyte used was LB-266 electrolyte prepared by Duoduo Chemical Reagents, and the negative electrode used was a lithium-boron alloy negative electrode disc with a diameter of 12 mm prepared in Example 2, or a pure lithium metal negative electrode disc with a diameter of 12 mm prepared in Comparative Example 1.

[0085] According to the above method, two full batteries were prepared, wherein the lithium boron alloy negative electrode in Example 2 was assembled into a LiB10% LFP full battery, and the pure lithium metal negative electrode prepared in Comparative Example 1 was assembled into a Li LFP full battery. The rate performance (1C = 170 mAh / g) of the two full batteries was tested at a voltage of 2.5-3.8 V under different conditions of 0.3C, 0.5C, 1.0C, 2.0C, 3.0C, 5.0C, and 10.0C.

[0086] Fig.12 a is the rate performance and coulombic efficiency data of LiB 10% LFP full battery and Li LFP full battery. Fig.12 b in the figure is a data graph of the discharge capacity of the LiB 10% LFP full battery and the Li LFP full battery under different rate conditions. According to the figure, it can be clearly observed that the lithium-boron alloy negative electrode of the present invention exhibits excellent discharge capacity at high rates, and exhibits discharge capacity of 139.1mAh / g, 139.1mAh / g, 130.2mAh / g, 111.6mAh / g, 89.2mAh / g, and 40.5mAh / g under 0.3C, 0.5C, 1.0C, 2.0C, 3.0C, and 5.0C. For the Li LFP full battery assembled with pure lithium metal negative electrode, the utilization rate of lithium decreases due to the presence of lithium dendrites. Under 3.0C conditions, the discharge capacity rapidly decays as the cycle proceeds, and under 5.0C conditions, the discharge capacity is only 2.9mAh / g. Therefore, the lithium-boron alloy negative electrode prepared by the present invention exhibits excellent high-rate capacity retention, and can be applied to the field of power batteries with higher rate performance requirements in the future.

[0087] Example 8

[0088] This example further explores the long cycle performance of the lithium-boron alloy negative electrode with a boron mass fraction of 10% prepared in the above Example 2 and the pure lithium metal negative electrode prepared in Comparative Example 1 in soft-pack batteries.

[0089] The lithium-boron alloy negative electrode with a boron mass fraction of 10% prepared in Example 2 and the pure lithium metal negative electrode prepared in Comparative Example 1 were assembled into soft-pack batteries respectively. The assembly method of the soft-pack battery is as follows: in a glove box filled with argon and having O2 <0.1ppm, H2O <0.1ppm, the positive electrode (using lithium iron phosphate, LFP) is cut into a rectangle of about 2×3cm, the diaphragm is cut into a rectangle of about 3×4cm using a 6mm microporous PP film (Celgard2400)), the negative electrode is cut into a rectangle of 2.5×3.5cm using the lithium-boron alloy negative electrode prepared in Example 2 or the pure lithium metal negative electrode prepared in Comparative Example 1, the positive and negative electrodes are respectively welded to the pole ears, stacked in sequence and placed in a sealed aluminum-plastic film, the electrolyte (using Duoduo Chemical Reagent LB-266 type electrolyte) is dripped and vacuum sealed to obtain a soft-pack battery.

[0090] Two soft-pack batteries were prepared according to the above method, wherein the lithium-boron alloy negative electrode in Example 2 was assembled into a LiB / / LFP soft-pack battery, and the pure lithium metal negative electrode prepared in Comparative Example 1 was assembled into a Li / / LFP soft-pack battery, and a long cycle performance test was carried out at 0.3C. Fig.13 a is the schematic diagram of LiB / / LFP soft pack battery and the long cycle performance diagram, Fig.13 b in the figure is a schematic diagram of a Li / / LFP soft-pack battery and a long cycle performance diagram. According to the figure, the capacity retention rate of the LiB / / LFP soft-pack battery after 30 cycles at 0.3C is 96.3%, and it can be stably cycled for more than 90 cycles, while the capacity retention rate of the Li / / LFP soft-pack battery after 30 cycles at 0.3C is 84.1%, followed by a significant capacity decay. This further proves the excellent ability of the lithium-boron alloy negative electrode prepared by the present invention to regulate the uniform deposition of lithium ions.

[0091] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a lithium-boron alloy negative electrode, characterized in that: Includes steps: The lithium metal and boron powder are sealed in a metal tube filled with an inert gas, the metal tube is vacuum-sealed in a quartz tube, and the quartz tube is calcined at a high temperature so that the lithium metal and boron powder in the metal tube are mixed and melted to obtain the lithium-boron alloy negative electrode.

2. The method for preparing a lithium-boron alloy negative electrode according to claim 1, characterized in that: The mass ratio of the lithium metal to the boron powder is 85-95:5-15.

3. The method for preparing a lithium-boron alloy negative electrode according to claim 1, characterized in that: The high temperature calcination temperature is 600° C. to 800° C., and the heat preservation time is 6 h to 8 h.

4. The method for preparing a lithium-boron alloy negative electrode according to claim 1, characterized in that: The metal tube is a niobium tube or a tantalum tube.

5. The method for preparing a lithium-boron alloy negative electrode according to claim 1, characterized in that: The inert gas is argon, and the pressure of the inert gas in the metal tube is 3×10 4 Pa~5×10 4 Pa; and / or the vacuum degree in the quartz tube is less than or equal to 1×10 5 Pa.

6. The method for preparing a lithium-boron alloy negative electrode according to claim 1, characterized in that: The step of calcining the quartz tube at a high temperature so that the lithium metal and the boron powder in the metal tube are mixed and melted to obtain the lithium-boron alloy negative electrode specifically includes: The quartz tube is calcined at 600° C. to 800° C. for 6 h to 8 h, so that the lithium metal and boron powder in the metal tube are mixed and melted to obtain a lithium-boron alloy block, and then the lithium-boron alloy block is repeatedly rolled to obtain a lithium-boron alloy negative electrode.

7. A lithium-boron alloy negative electrode, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 6.

8. The lithium-boron alloy negative electrode according to claim 7, characterized in that: The mass fraction of boron in the total mass of the lithium-boron alloy negative electrode is 5% to 20%.

9. The lithium-boron alloy negative electrode according to claim 7, characterized in that: The surface of the lithium-boron alloy negative electrode has a nanofiber structure, and the fiber diameter of the nanofiber structure is 20nm-100nm.

10. A lithium metal battery, characterized in that: Comprising the lithium-boron alloy negative electrode as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of lithium-boron alloy and reactor

    CN107858544A

  • Electrode material lithium boron and preparation method thereof

    CN112624135A

  • Boron-containing composite lithium metal negative electrode material as well as preparation method and application thereof

    CN118367135A